The Swedish Debate on Tuition Fees for International Students in Higher Education - Nilsson, Per A.; Westin, Lars (Journal of Interdisciplinary Studies in Education, 2023)
In 2009, the Swedish parliament decided to introduce tuition fees for students from outside the European Economic Area (EEA) and Switzerland. The first tuition-students arrived in 2011. A direct consequence was a decrease by 80 percent of incoming students. The decision by the lawmakers was debated and questioned by business leaders, students, and representatives for higher education institutions (HEI). In this reflection paper, we present the most common issues in that debate and reflect on those arguments ten years after tuition fees were introduced. The debate in Sweden prior to the reform and the following development represents an interesting case that illustrates some of the dynamics of international student mobility and the impacts this may have on HEI.